Ketimpangan Job Fair dan Ketidakpedulian Struktural Pemerintah terhadap Pengangguran di Indonesia - Lawalu, Emiliana Martuti; Tanau, Maria Karolina; Emilrensi, Anasthasya Nathaleoni; Bolla, Larasti Viktoria; Kabba, Melkianus Nedi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research examines the inequality of job fairs and the structural indifference of the Indonesian government towards unemployment, with a focus on the mismatch between labor market needs and the job market policies. The study uses a descriptive qualitative approach through library research, focusing on the exploration of concepts, theories, and a critical analysis of the phenomena of job fair inequalities and the government's labor policies in the context of structural unemployment in Indonesia. The primary aim of the research is to explore how government policies, including job fairs, either exacerbate or alleviate structural unemployment in Indonesia. This study relies on secondary data sources, including official government documents (e.g., reports from Statistics Indonesia and the Ministry of Manpower), media articles, and scholarly literature. Data is collected through documentation and content analysis techniques. The data is analyzed using content analysis and thematic analysis techniques, which include data reduction, categorization, interpretation, and conclusion formulation. The findings show a significant disparity between job opportunities provided by job fairs and the actual labor market needs, highlighting a critical gap in government policies. Structural indifference, particularly in policy implementation and adaptation, is evident in the mismatch between educational outcomes and employment opportunities.